Molecular Mechanisms of Proteinuria in Focal Segmental Glomerulosclerosis - Wen, Yumeng; Shah, Sapna; Campbell, Kirk N. (Frontiers in Medicine, 2018)
Focal segmental glomerulosclerosis (FSGS) is the most common primary glomerular disease resulting in end-stage renal disease in the US and is increasing in prevalence worldwide. It is a diverse clinical entity with idiopathic, genetic, metabolic, infectious and other causes that culminate in a characteristic histologic pattern of injury. Proteinuria is a hallmark of FSGS as well as other primary and secondary glomerular disorders. The magnitude of proteinuria at disease onset and during treatment has prognostic implications for renal survival as well as associated cardiovascular morbidity and mortality. Significant advances over the last two decades have shed light on the molecular architecture of the glomerular filtration barrier. The podocyte is the target cell for injury in FSGS. A growing list of disease-causing gene mutations encoding proteins that regulate podocyte survival and homeostasis have been identified in FSGS patients. Several pathogenic and regulatory pathways have been uncovered that result in proteinuria in rodent models and human FSGS. The recurrence of proteinuria and FSGS after kidney transplantation is supporting evidence for the role of a circulating permeability factor in disease pathogenesis. These advances reviewed herein, have significant implications for disease classification and therapeutic drug development for FSGS.